Análisis de los factores que influyen en las empresas Pymes manufactureras de alimentos del Valle del Cauca para su internacionalización a través de la exportación. (2023)
SME companies in Colombia have contributed to the growth of the country's economy, therefore, since the year 2000, when they were legally recognized, their development and growth has increased, and thanks to this growth, they are considered one of the most important productive sectors in the country. which, the government has developed different strategies and laws that benefit these companies so that they continue with their economic activity and internationalize their products. These companies for the year 2021 contributed 40% of the country's GDP (ANIF, 2021), but in the analysis carried out based on foreign trade statistics, specifically for exports, the representation is minimal, so an analysis is carried out. research to identify the factors that prevent and negatively influence these companies at the time of exporting